Psychological healing function of poetry appreciation based on educational psychology and aesthetic analysis - Zhang, Weijin (Frontiers in Psychology, 2022)
With the development of society, the rapidly developing social environment has played a significant role in the special group of college students. As a member of society, college students will inevitably suffer certain setbacks and psychological obstacles in their study and life. Based on this, this work aims to solve various mental illnesses caused by anxiety and confusion of college students during the critical period of social transformation. Educational psychology theory and aesthetic theory combined with poetry appreciation are applied to the mental health education of college students to obtain a satisfying psychological healing effect. First, this work summarizes the connotation and characteristics of college students' mental health and defines educational psychology. Secondly, the long tradition of Chinese poetry teaching is introduced, the theoretical basis of poetry therapy and aesthetic psychology is expounded, and foreign poetry is discussed. In addition, the method of using poetry appreciation to promote personality shaping and psychological healing of college students is proposed based on the theory of educational psychology and the theory of poetry appreciation psychotherapy. In addition, the concept of mental health education for college students is studied from the perspectives of mental health, mental health education, college students' mental health education, and appreciation of ancient poetry. In addition, the principle and significance of college students' mental health education are discussed from the perspective of poetry appreciation. Finally, an experimental study is conducted on college students and patients in a certain department of a hospital by issuing questionnaires to verify the practical application effect of this method in psychotherapy. The survey results indicate that the scores of college students who have completed a one-semester poetry appreciation course in different dimensions of mental disorders are lower than those of those who have not completed the course. At the same time, in the scores of 16 personality traits, the positive trait scores of the experimental group are higher than those of the control group.